2023
DOI: 10.3390/molecules28020830
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Novel Thiosalicylate-based Solid-Supported Ionic Liquid for Removal of Pb(II) Ions from Aqueous Solution

Abstract: The main objectives of this study are to synthesize a new solid-supported ionic liquid (SSIL) that has a covalent bond between the solid support, i.e., activated silica gel, with thiosalicylate-based ionic liquid and to evaluate the performance of this new SSIL as an extractant, labelled as Si-TS-SSIL, and to remove Pb(II) ions from an aqueous solution. In this study, 1-methyl-3-(3-trimethoxysilylpropyl) imidazolium thiosalicylate ([MTMSPI][TS]) ionic liquid was synthesized and the formation of [MTMSPI][TS] wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The FTIR analysis of [HIMP][TS] ionic liquid showed absorption bands at 2958 cm −1 corresponding to -CH 2 stretching, 1628 cm −1 for C-N stretching, and a small peak protruded at 2232 cm −1 for the S-H group. This is in accordance with the synthesis of thiosalicylate ionic liquid from a previous study [17]. The O-H vibration in PVA-alginate-[HIMP][TS] decreased, indicating an interaction with the imidazolium cation.…”
Section: Characterisation Of [Himp][ts] and Pva-alginate-[himp][ts]supporting
confidence: 91%
“…The FTIR analysis of [HIMP][TS] ionic liquid showed absorption bands at 2958 cm −1 corresponding to -CH 2 stretching, 1628 cm −1 for C-N stretching, and a small peak protruded at 2232 cm −1 for the S-H group. This is in accordance with the synthesis of thiosalicylate ionic liquid from a previous study [17]. The O-H vibration in PVA-alginate-[HIMP][TS] decreased, indicating an interaction with the imidazolium cation.…”
Section: Characterisation Of [Himp][ts] and Pva-alginate-[himp][ts]supporting
confidence: 91%
“…The chemical compounds utilized in this study were supplied by Sigma Aldrich, SRL chemicals Scienti c, and Lichro Chemicals with a stated purity and are listed in S. Table 1. [35] was used for the preparation of this IL. An aqueous solution of sodium salicylate (0.05 mol in 50 mL deionized water) was added slowly to an aqueous solution of a Chloride-based IL (0.05 mol in 100 mL deionized water) in a 250 mL RBF.…”
Section: Methodsmentioning
confidence: 99%
“…The higher the initial concentration, the higher removal capacities achieved by Si-Sal-SSIL in extracting Pb(II) ions from aqueous solution due to the vacant spaces available on the surface of adsorbent. 44 However, it can be seen that the removal percentages decreased with increasing initial concentration of metal ions solution due to the competition for adsorption sites among the metal ions. 11, showed that the removal efficiencies of Si-Sal-SSIL on the rst and second cycles decreased slightly by 1-2% for Pb(II) and Ni(II) ions.…”
Section: Adsorption Isothermmentioning
confidence: 98%
“…Published by the Royal Society of Chemistry isotherm was developed for the homogeneous system, and it gives concept of monolayer adsorption of solute on the surface of sorbent. 44 Distribution of metal ions between liquid and solid surface was calculated by eqn ( 5) and (6). The important feature of Langmuir is commonly presented in terms of dimensionless separation factor, R L .…”
Section: Evaluation Of the Adsorption Data Through Isotherm Tting Mo...mentioning
confidence: 99%